2001
DOI: 10.1016/s0029-7844(00)01097-8
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder and pregnancy complications

Abstract: Pregnant women with posttraumatic stress disorder might be at higher risk for certain conditions, and assessment and treatment for undiagnosed posttraumatic stress might be warranted for women with those obstetric complications. Prospective studies are needed to confirm present findings and to determine potential biologic mechanisms. Treatment of traumatic stress symptoms might improve pregnancy morbidity and maternal mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
97
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(102 citation statements)
references
References 18 publications
2
97
0
3
Order By: Relevance
“…Posttraumatic stress disorder (PTSD) has been posited as the primary mechanism whereby lifetime trauma exposure affects health [4]. Women diagnosed with PTSD are at greater risk of pregnancy-related complications, and high levels of PTSD have been reported in lowincome African American women [49,50]. Moreover, African American women who live and repeatedly interact in violent environments, as suggested by our findings, may be at risk for a multitude of deleterious health effects, such as posttraumatic stress symptoms.…”
Section: Discussionmentioning
confidence: 54%
“…Posttraumatic stress disorder (PTSD) has been posited as the primary mechanism whereby lifetime trauma exposure affects health [4]. Women diagnosed with PTSD are at greater risk of pregnancy-related complications, and high levels of PTSD have been reported in lowincome African American women [49,50]. Moreover, African American women who live and repeatedly interact in violent environments, as suggested by our findings, may be at risk for a multitude of deleterious health effects, such as posttraumatic stress symptoms.…”
Section: Discussionmentioning
confidence: 54%
“…Nine studies were excluded because they reported posttraumatic stress symptoms in relation to gynecological or obstetric aspects other than regular childbirth, such as spontaneous abortion, pregnancy loss, stillbirth, obstetric and/or gynecological procedures (not related to childbirth), tokophobia and pregnancy complications (Bowles et al, 2000;Engelhard et al, 2001;Hofberg & Brockington, 2000;Holditch-Davis et al, 2003;Hunfeld et al, 1997;Menage, 1993;Pierrehumbert et al, 2003;Seng et al, 2001;Turton et al, 2001). One study was excluded because it focused specifically on parents of infants with a high-risk birth (DeMier, Hynan, Harris, & Manniello, 1996) and another because it focused on stressful life events related to childbearing (Arizmendi & Affonso, 1987).…”
Section: Resultsmentioning
confidence: 99%
“…[60][61][62][63][64] Traumatic life events are also associated with pregnancy complications, including miscarriage, highrisk pregnancy, hyperemesis, preterm contractions, 65 and delivery complications. [66][67][68][69][70][71] Perinatal depression and eating disorder comorbidity Perinatal depression is common in women with an ED history. [10][11][12][13][14][15][16][17] 75 …”
mentioning
confidence: 99%